Labour market feminization and economic development in sub-Saharan Africa - Adejumo, Oluwabunmi O.; Obisanya, Joshua F.; Akinyemi, Folashade O. (International journal of manpower, 2024)
PurposeWomen’s direct or subtle exclusion from the labour market is still evident, necessitating more rigorous inquiries into the subject matter. The study aims to assess the moderating factors that can boost the inclusion of women participation in the labour market by complementing and actualising the doctrine of the feminist U-shaped hypothesis.Design/methodology/approachThis study is situated within the feminist U-shaped hypothesis and employs the generalised method of moments (GMM) on 38 countries in sub-Saharan Africa (SSA).FindingsThis study validates the U-shaped labour hypothesis and expands on the moderating effects of the U-shaped curve in 38 SSA countries.Originality/valueThe study contributes to the influences of human capital development and technological access that can significantly improve the workings of the feminist U- hypothesis in SSA countries.